Particularities of the integration process of the adopted condition children (Journal of Parents and Teachers, 2012)
Adoption is a challenging process that can end up in so many different ways. Some children had lived a terrible life before the adoption. In this article the author talks about the difficulty of the integration of the kids and also about the different phases of adaptation that the kid might experience.
Keywords: Adoption; integration; personal relationships; phases.